2016
DOI: 10.1007/s15010-016-0910-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of urinary tract infections and antibiotic resistance in the outpatient setting: a cross-sectional study

Abstract: ESBL had been found in a community population, and even though the rate was low, it represents a warning and confirms that surveillance should continue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 27 publications
4
32
0
6
Order By: Relevance
“…Another author confirmed that only four pregnant patients with UTI were included in their study and none of them were diagnosed to have bacterial culture indicating ESBL infection . In one study from France, of nine pregnant patients, five had positive urine cultures and none of them were ESBL producers . The authors of eight studies did not reply …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Another author confirmed that only four pregnant patients with UTI were included in their study and none of them were diagnosed to have bacterial culture indicating ESBL infection . In one study from France, of nine pregnant patients, five had positive urine cultures and none of them were ESBL producers . The authors of eight studies did not reply …”
Section: Resultsmentioning
confidence: 97%
“…50 In one study from France, of nine pregnant patients, five had positive urine cultures and none of them were ESBL producers. 51 The authors of eight studies did not reply. 52-59 Figure 1 shows the flowchart that describes the process of inclusion of the studies.…”
Section: Esbl-producing Enterobacteriaceaementioning
confidence: 99%
“…Still, current trends show increasing rates of resistance to various antimicrobial agents independently of pathogen all over the world. The effective initial treatment of UTI might prevent the rapidly increasing bacterial resistance to antimicrobial drugs [8, 10]. Hooton et al [11] postulated in 2004 that increased use of fluoroquinolones would lead to decrease of efficacy to this class of antimicrobial drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Disk-diffusion tests were used for resistance and susceptibility testing with application of appropriate disks, including ampicillin (10  μ g), trimethoprim/sulfamethoxazole (11.25  μ g/23.75  μ g), ciprofloxacin (5  μ g), amoxicillin/clavulanic acid (20  μ g/10  μ g), nitrofurantoin (100  μ g), cephalexin (30  μ g), and cefuroxime (30  μ g). Extended-spectrum β -lactamase (ESBL) isolates were identified by specific polymerase chain reaction (PCR) and sequencing as described in the literature [8]. The obtained isolates were identified using standard methods, via a commercial bacterial identification system (Vitek 2 Compact, BioMérieux, France).…”
Section: Methodsmentioning
confidence: 99%
“…Among the etiological factors inflammatory processes of reproductive system are multi-resistant factors or L-forms (protozoare, bacteria, fungi, viruses) with modified biological properties in the numerous microbe association are found more frequently, partially due to the non-systemic and unjustified administration of antibiotics, hormonal preparations, cytokines etc. [6,27].…”
Section: Etiological Factors Of Inflammatory Process Of Reproductive mentioning
confidence: 99%